Dynamics of a pile-moored fish cages in current and waves: A numerical study. (1st February 2023) - Zitti, Gianluca; Novelli, Nico; Brocchini, Maurizio
Abstract: We propose a numerical study of the dynamics of a double-constrained cylindrical pile-moored fish-farm cage, to be possibly installed at the foundations of dismissed offshore structures. Our model, derived from the net-truss model of Kristiansen and Faltinsen (2012), takes into account the elasticity of the net material, the real size of the net and is applied with and without mesh-grouping approaches, this allowing us to evaluate the range of validity of mesh-grouping techniques. First, cage dynamics have been studied with small-scale tests, in which the numerical model accurately reproduces the behaviour of the cage in both sea currents (velocity in the range 0 . 5 − 1 m/s ) and waves of small amplitude (with height of 1 m and period in the range 4 − 32  s). Use of the net real size for the computation grid of small-scale tests allows for identification of the main phenomena influencing the load distribution and the volume loss, which are: the dominant sail-shape deformation in the streamwise direction, the flattened deformations in the cross flow direction, and high-frequency oscillations in the vertical direction in long waves. Subsequently, a prototype-scale test is run to simulate the dynamics of a realistic installation of a double-constrained cylindrical pile-moored fish-farm cage in the Adriatic sea (considering both 1 m/s sea current and storm sea state characterized by a peak period T p = 4  s and significant wave height H s = 1 . 5  m), showing that the major loads are a compression load on the pile up to 1 kN and a bending moment at the pile base up to 9.1 kNm. The proposed configuration always showed a small net relative volume loss V L < 5 % . Highlights: The dynamics of a pile-moored fish-farm cage is studied numerically. Small-scale tests (with real size of the net) and large-scale test (with grouping method) are performed. The numerical model accurately reproduces the dynamics of the cage forced by sea currents and linear waves. Cage dynamics is dominated by streamwise sail-type deformation and crossflow flattened deformation. The net of a realistic installation in the Adriatic sea generates a compression load (up to 1 kN) and a bending moment (up to 9.1 kN m).